2020
DOI: 10.1101/2020.10.08.20209072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating the impact of disruptions due to COVID-19 on HIV transmission and control among men who have sex with men in China

Abstract: Introduction The COVID-19 pandemic is impacting HIV care globally, with gaps in HIV treatment expected to increase HIV transmission and HIV-related mortality. We estimated how COVID-19-related disruptions could impact HIV transmission and mortality among men who have sex with men (MSM) in four cities in China. Methods Regional data from China indicated that the number of MSM undergoing facility-based HIV testing reduced by 59% during the COVID-19 pandemic, alongside reductions in ART initiation (34%), numbe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
1
11
0
2
Order By: Relevance
“…The rules were vital for COVID-19 containment but seriously affected other public health systems and HIV care services [ 6 ]. Furthermore, HIV-related deaths and new HIV infections were expected to increase with the duration of pandemic COVID-19 due to the interruption of antiretroviral therapy (ART) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rules were vital for COVID-19 containment but seriously affected other public health systems and HIV care services [ 6 ]. Furthermore, HIV-related deaths and new HIV infections were expected to increase with the duration of pandemic COVID-19 due to the interruption of antiretroviral therapy (ART) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that HIV testing rates decreased by 36.7% during the COVID-19 pandemic in China compared with the first quarter of 2019 [ 16 ]. Another study also observed a 59% decrease in the number of MSM undergoing facility-based HIV testing and a 34% reduction in ART initiation rate during the implementation of COVID-19 measures in Jiangsu province [ 8 ]. Meanwhile, PLWH faced the risk of ART interruption and disruption in chronic conditions treatment as hospitals were closed and some medical resources were re-purposed for COVID-19 cases [ 17 – 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Die Daten zur Impfbereitschaft im Gesundheitswesen sind aber noch sehr begrenzt. Studien aus China und der Trkei berichten von einer Bereitschaft zur SARS-CoV-2-Impfung unter Angestellten im Gesundheitswesen von ca.70% [ 18 , 19 ] und in Frankreich von 76,9% [ 20 ]. Der Anteil der impfbereiten Augenrzte in unserer Studie ist somit vergleichsweise hoch.…”
Section: Diskussionunclassified
“…Wie in der Allgemeinbevlkerung (s.oben) wird in Publikationen aus Israel, der Trkei, USA und China eine Abhngigkeit der Impfbereitschaft bei Angestellten im Gesundheitswesen von Alter und Geschlecht beschrieben, auerdem aber auch von der Berufsgruppe (rzte, Pflege, Auszubildende, Sonstige), von der jeweiligen medizinischen Fachrichtung und von der direkten Arbeit mit COVID-19-positiven Patienten oder der subjektiven Risikobewertung [ 18 22 ]. Tendenziell wrden sich in Umfragen unter Angestellten im Gesundheitssektor Mnner, ltere Personen und Personen, die das persnliche Risiko z.B.…”
Section: Diskussionunclassified
“…These COVID-19 measures are extremely important for COVID-19 control, but it also seriously impacted other public health services including services for HIV care continuum [6]. According to some modelling studies, HIV related deaths and new HIV infection will increase with the duration of pandemic COVID-19 because of the interruption of antiretroviral therapy (ART), compared with if there was no COVID-19 pandemic [7][8].…”
Section: Introductionmentioning
confidence: 99%